1998
DOI: 10.2307/1592712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibody Responses of Emus (Dromaius novaehollandiae) to Avian Influenza Virus Infection

Abstract: Emu antibody responses to avian influenza virus (AIV) infection were evaluated by the competitive enzyme-linked immunosorbent assay (C-ELISA), agar gel immunodiffusion (AGID) and hemagglutination inhibition (HI) tests. All birds infected with AIV H5N1, H5N3, or H7N7 developed antinucleoprotein (NP) antibodies as early as 7 days postinfection as detected by the C-ELISA. The responses lasted 49 days for the emus receiving H5N3 and at least 56 days for emus receiving the other two viruses. By evaluating 50 emu fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, the HI test detected infection more frequently when compared with the C-ELISA and the AGID test. Previous studies in testing emu sera found more positive results with the HI test rather than the C-ELISA, with a relative sensitivity for the C-ELISA of 95.7% (Zhou et al, 1998). Unfortunately, HI cannot be used for surveillance because each individual test will detect only one haemagglutinin subtype and test accuracy is greatly affected by non-specific agglutination factors present in ostrich sera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the HI test detected infection more frequently when compared with the C-ELISA and the AGID test. Previous studies in testing emu sera found more positive results with the HI test rather than the C-ELISA, with a relative sensitivity for the C-ELISA of 95.7% (Zhou et al, 1998). Unfortunately, HI cannot be used for surveillance because each individual test will detect only one haemagglutinin subtype and test accuracy is greatly affected by non-specific agglutination factors present in ostrich sera.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to the typespecific nucleoprotein of AIV were determined using the agar gel immunodiffusion test (Beard, 1970) using commercially available reagents (Charles River SPAFAS Laboratory, Storrs, CT, USA). The C-ELISA was carried out as described by Zhou et al (1998).…”
Section: Serological Testsmentioning
confidence: 99%
“…Based on the study that the emu is a host for avian influenza viruses, 14 emu fibroblast cells were chosen to test the specificity of MAbs. Secondary emu fibroblast cell cultures were infected with selected AIV subtypes (H3N2, H4N2, H6N8, and H7N2) at 1/100 dilution and then harvested after 24 hr.…”
Section: Indirect Fluorescent Flow Cytometrymentioning
confidence: 99%
“…Antibody titer in serum was determined by an ELISA. 14 Mice were boosted again by injecting intraperitoneally 20 g of H antigen in PBS (200-400 l), and cell fusion was performed 3 days after the immunization. Hybridomas were generated by fusion of the Sp2/0-Ag14 mouse myeloma cell line and spleen cells from boosted BALB/C mice.…”
Section: Preparation Of Monoclonal Antibodiesmentioning
confidence: 99%
“…The cELISA has been evaluated for use with chickens, turkeys, game birds, ratitites and penguins (Shafer, Katz & Eernisse, 1998). In these avian species, the cELISA was more sensitive and more specific than the AGID test (Shafer, Katz & Eernisse, 1998), as sensitive and specific as the HI test (Shafer, Katz & Eernisse, 1998), and able to detect some antibodies earlier in infection than the AGID and HI tests (Zhou et al ., 1998). While the cELISA has only been evaluated for use with avian sera, the bELISA has been used to assess exposure of some mammals to human and swine influenza viruses.…”
Section: Introductionmentioning
confidence: 99%